Internalisasi Nilai Anti Korupsi dengan Model Nampe Guna Meningkatkan Perilaku Anti Korupsi Mahasiswa Program Studi Teknik Informatika Universitas PGRI Madiun - Muhammad Hanif (Universitas Pancasakti Tegal, 2021)
The purpose of this study is to improve the anti-corruption behavior of students of the Informatics Engineering StudyProgram at the Universitas PGRI Madiun through the internalization of anti-corruption values with the Nampe Model.The research was Classroom Action Research. Data were collected qualitatively by using observation, tests, and non-tests,while the data analysis used descriptive statistics. Based on the research carried out for two cycles, it was found that the anticorruptionbehavior of students increased after internalizing the anti-corruption values with the Nampe Model. Thisincrease is shown by the assessment of anti-corruption behavior in pre-cycle at 30.4%, increased to 62.2% in cycle 1 and at78.2% in cycle 2. The average value of all domains also increases, such as; (a) affective domain in pre-cycle at 59.1, cycle 1at 65.5, and cycle 2 at 75.5 (b) cognitive domain in pre-cycle at 78.9, cycle 1 at 82.4, cycle 2 at 85, 4, (c) psychomotordomain in pre-cycle at 62.44, cycle 1 at 66, cycle 2 at 75.6. The increase in anti-corruption behavior is also shown by theaverage score of the anti-corruption component in pre-cycle at 62.4, cycle 1 at 66.4, and cycle 2 at 77.1.